THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF THE OFFICE OF THE REGIONAL LIBRARY AND ARCHIVES OF GOWA REGENCY - Amraeni Amraeni; Muhlis (Adisam Publisher, 2025)
The purpose of this study was to determine how much influence work discipline has on the performance of employees of the Regional Library and Archives Office of Gowa Regency. The population of this study were all employees of the Regional Library and Archives Office of Gowa Regency. While the sampling method used is the slovin method, so that the number of samples is determined as many as 30 people. To obtain the required data, the data collection methods used are observation, questionnaires and interviews. While the analysis method used is quantitative descriptive analysis, simple regression analysis and hypothesis testing. Based on the results of the research analysis on the effect of work discipline on employee performance at the Office of the Regional Library and Archives of Gowa Regency, this can be seen from the t test which shows that there is a positive effect of work discipline on the performance of employees of the regional library and archives office of Gowa Regency at 0.003 <0.005 and the value of T Count. 0.005 and the T Count value of 3.325> the T Table value of 2.052, the t test shows that there is a positive effect of work discipline on employee performance at the library and archives office of the Gowa Regency area of 0.000 <0.05 and the T Count value of 4.963> the T Table value of 2.052. Sadangakan from the results of the coefficient of determination (R2). Based on the results of the above analysis, it shows that performance and work discipline are able to explain the achievement variable, amounting to 53.9% while the rest can be explained by other variables not examined.